2021
DOI: 10.1111/jnc.15461
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron enrichment attenuates α‐synuclein spreading after injection of preformed fibrils

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 121 publications
1
15
0
Order By: Relevance
“…A previous study showed that intranasal injection of αsynuclein PFFs induced microglial iron deposition in monkeys (Guo et al, 2021). Combining the results of these two recent studies, where α-synuclein was shown to induce iron accumulation (Guo et al, 2021) but the iron elevation was shown to slow α-synuclein spreading (Joppe et al, 2021), suggests that α-synuclein may precede the iron accumulation during the progress of PD.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…A previous study showed that intranasal injection of αsynuclein PFFs induced microglial iron deposition in monkeys (Guo et al, 2021). Combining the results of these two recent studies, where α-synuclein was shown to induce iron accumulation (Guo et al, 2021) but the iron elevation was shown to slow α-synuclein spreading (Joppe et al, 2021), suggests that α-synuclein may precede the iron accumulation during the progress of PD.…”
mentioning
confidence: 78%
“…Lewy body pathology has been shown to be transmitted between brain regions (Hijaz & Volpicelli‐Daley, 2020), it remains unknown what impact iron may have on this pathology spreading. In a recent study published in the Journal of Neurochemistry , Joppe and colleagues (Joppe et al., 2021) found that in a mouse model of intrastriatal α‐synuclein preformed fibrils (PFFs) injection, the propagation of pathological α‐synuclein marked as α‐synuclein phosphorylated at serine 129 (pS129) was decreased in mice that had brain iron elevation induced by neonatal iron feeding (Figure 1). The long‐term memory but not motor function showed impairment at 90 days after α‐synuclein PFFs injection with or without iron feeding.…”
Section: Figurementioning
confidence: 99%
“…Moreover, PD patients show elevated Fe levels both in the NM neurons and immediately adjacent surrounding tissue (Oakley et al., 2007). Interestingly, iron interacts with alpha‐synuclein (reviewed in Lingor et al., 2017; Joppe et al., 2019) and an increase in brain iron alters alpha‐synuclein aggregation (Dauer Née Joppe et al., 2021). There is thus compelling evidence of Fe accumulation in the SN of PD patients, and this excess Fe can be visualized using magnetic resonance imaging (MRI) (Li et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the link between iron and α‐syn goes deeper than this. A recent study reported that iron enrichment occurring in particular areas of PD brains affected the spreading pathology of α‐syn in mice models 180 . Striatal iron retention alters the connectivity of the brain connectome, leading to a redistribution of α‐syn aggregates in the brain, or rather the restriction of phosphorylated α‐syn spread.…”
Section: Iron Metabolism In Brain Diseasesmentioning
confidence: 99%